Effects of dietary n-3 highly unsaturated fatty acids on growth, non-specific immunity, expression of some immune-related genes and resistance to Vibrio harveyi in hybrid grouper (♀ Epinephelus fuscoguttatus × ♂ Epinephelus lanceolatu). Issue 96 (January 2020) - An, Wenqiang; Dong, Xiaohui; Tan, Beiping; Yang, Qihui; Chi, Shuyan; Zhang, Shuang; Liu, Hongyu; Yang, Yuanzhi
Abstract: This study was conducted to investigate the effects of dietary n-3 highly unsaturated fatty acids (n-3 HUFA) on growth performance, non-specific immunity, expression of some immune-related genes and resistance to Vibrio harveyi in juvenile hybrid grouper (♀ Epinephelus fuscoguttatus × ♂ Epinephelus lanceolatu ). Six isoproteic and isolipidic experimental diets were formulated with graded levels of n-3 HUFA (0.65, 1.00, 1.35, 1.70, 2.05 and 2.40% of dry matter, respectively), and the 0.65% group was used as control group. Each diet was randomly allocated to triplicate groups of fish in 1000 L fiberglass tank, and each tank was stocked with 40 fish (initial weight 12.06 ± 0.01 g) for 8 weeks. Results showed that feed conversion ratio (FCR), survival rate (SR), hepatosomatic index (HSI) and condition factor (CF) were all not significantly affected by dietary n-3 HUFA levels ( P > 0.05). Weight gain (WG) and specific growth rate (SGR) in 1.35% group were significantly higher than those in 2.40% group ( P < 0.05). Crude lipid of body in 1.00% group was significantly lower than that in 1.70% and 2.40% groups ( P < 0.05). Liver and muscle fatty acid profiles reflected that of diets. Before challenge with Vibrio harveyi, the activity of serum superoxide dismutase (SOD), catalase (CAT) and content of complement 3 (C3) in 1.35% and 1.70% groups significantly higher than those of control group ( P < 0.05). After challenge with Vibrio harveyi, serum CAT, glutathione peroxidase (GSH-PX), lysozyme (LZM) and C3 all increased sharply, while SOD showed the opposite trend. Before challenge with Vibrio harveyi, the expression levels of intestine toll-like receptor 22 (TLR22) and myeloid differentiation factor 88 (MyD88) mRNA in 2.40% group were significantly increased, and the expression levels of tumour necrosis factor α (TNF-α) and interleukin 1β (IL-1β) mRNA in 2.05% group were significantly higher than those in 1.00% and 1.35% groups ( P < 0.05). In addition, the TLR22 and IL-1β mRNA levels in kidney of 1.70% group were significantly lower than those in control group ( P < 0.05). After challenge with Vibrio harveyi, the expression level of MyD88 mRNA in intestine of 1.35% group was significantly higher than that in 1.00% group and from 1.70% to 2.40% groups ( P < 0.05), while TNF-α and IL-1β obtained minimum values in 1.70% group. In the kidney, the interleukin 10 (IL10) mRNA expression was significantly higher in 1.70% group than that in other groups, while the IL-1β expression in 1.70% group was on the contrary and significantly lower than that in 2.40% group ( P < 0.05). Results of this study suggested that moderate dietary n-3 HUFA (1.47%–1.70% HUFA) could improve the growth performance, non-specific immunity and inhibit the inflammatory response of hybrid grouper. Highlights: The results of this experiment showed that the optimal WG of hybrid grouper based on quadratic regression analysis was 1.47% n-3 HUFA on the base of dry matter. High levels of n-3 HUFA could lead to the oxidative stress response. Moderate levels of n-3 HUFA could decrease the gene expressions of the toll-like receptor 22 and myeloid differentiation factor 88 in intestine and kidney. Moderate levels of n-3 HUFA could improve the disease resistance of hybrid grouper.